Improving Healthcare Patient Data Security: An Integrated Framework Model For Electronic Health Records From A Legal Perspective - Lestari, Ahdiana Yuni; Misran, Misran; Raharjo, Trisno; Annas, Muhammad; Riskanita, Dinda; Prabandari, Adya Paramita (LAW REFORM, 2024)
This study aims to critically examine the legal responsibilities of healthcare facilities in Indonesia regarding the protection of patient data within Electronic Medical Records (EMR). The research employs a mixed-method approach, combining normative legal analysis with empirical data collection from healthcare facilities to assess the implementation of data protection regulations. The findings reveal significant gaps in the enforcement of Minister of Health Regulation Number 24 of 2022 and Law Number 27 of 2022 concerning Personal Data Protection, particularly in smaller clinics and independent practices. These facilities often lack the technical infrastructure and resources required to meet regulatory standards, resulting in inconsistencies in data protection and a higher incidence of data breaches. The study introduces the Integrated Security and Usability Framework for Electronic Medical Records (ISU-EMR), which combines the principles of the Confidentiality, Integrity, and Availability (CIA) Triad with Human-Computer Interaction (HCI) Theory. This framework addresses both the technical and human factors contributing to data breaches, offering a balanced solution for enhancing data protection while maintaining usability in EMR systems. The implications of this research extend to both theory and practice, providing a new model for data protection in healthcare that can be adapted to various settings.